Elimination of power divergences in consistent model for spinless and high-spin particle interactions - Kulish, Yu.V.; Rybachuk, E.V. (Вопросы атомной науки и техники, 2007)
The currents for the interaction of the massive high-spin boson (J≥1) with two spinless particles are derived. These currents obey the theorem on currents and fields as well as the theorem on current asymptotics. In one-loop approximation the contributions of high-spin boson to the self-energy operator for a spinless particle are calculated. It is shown that in one loop approximation the high-spin boson contributions for any spin J and mass lead to finite self-energy operators of spinless-particle.